Modified diaphragm for polyanion solid sodium battery and preparation method of modified diaphragm
By using a modified separator with a coordinated cooperation between the solid electrolyte layer and the gel electrolyte layer in sodium ion batteries, the shortcomings of sodium ion batteries in terms of rate performance, energy density and cycle life are solved, and the battery performance is improved and the safety performance is achieved. improve.
Patent Information
- Application Number
- CN202411716169.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-25
AI Technical Summary
Existing sodium ion batteries have shortcomings in rate performance, energy density and cycle life, and the thermal stability and safety performance of the diaphragm need to be further improved.
The solid electrolyte layer and gel electrolyte layer are combined to combine oxide solid electrolyte and polymer solid electrolyte to modify the separator to improve the transmission rate and diffusion coefficient of sodium ions, extend the cycle life of the battery, and improve the thermal stability of the separator. and puncture resistance.
The rate performance and low-temperature performance of sodium ion batteries are improved, the cycle life of the battery is extended, the thermal stability and safety performance of the diaphragm are improved, the use of liquid electrolytes is reduced, and the energy density of the battery is increased.
Smart Images

Figure BDA0005156924590000131 
Figure BDA0005156924590000141
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a modified diaphragm for a polyanion solid-state sodium battery and a preparation method thereof. Background Art
[0002] In recent years, factors such as global lithium ore shortage, large price fluctuations and fierce market competition have limited the development speed of lithium-ion batteries. At the same time, sodium metal has great research and development potential due to its abundant resources, wide distribution and low price. Compared with lithium ions, sodium ions have a smaller Stokes radius, which is conducive to the improvement of electrical conductivity. This feature is of great help to the charge and discharge cycle of sodium ion batteries under low temperature and high rate conditions. In addition, sodium batteries are also significantly lower than lithium batteries in terms of thermal controlled temperature, so they perform well in tests such as puncture, extrusion, and overcharge.
[0003] Although sodium-ion batteries have many advantages, there are still certain problems in practical applications. First, the energy density of sodium batteries is lower than that of lithium-ion batteries. In addition, compared with lithium iron phosphate batteries, sodium batteries have a shorter cycle life. In the selection of the four major consumables of positive and negative electrode materials, electrolytes and separators, most sodium-ion batteries have adopted the research and development model of lithium-ion batteries. Among the various negative electrode materials, hard carbon (HC) has become the current mainstream choice due to its highly competitive electrochemical properties. There are currently three options on the positive electrode side, layered transition metal oxides, Prussian blue and polyanion positive electrode materials. Among them, polyanion positive electrode materials have excellent stability and cycle performance compared to other positive electrode materials. Among the many polyanion positive electrode materials, sodium iron pyrophosphate (NFPP) has an intrinsically stable covalent bond structure, which makes the sodium iron pyrophosphate system have a longer cycle life. However, the electronic conductivity of the NFPP native material is poor, and the rate performance and low-temperature performance are poor, which is contrary to the intrinsic advantages of sodium-ion batteries. Therefore, sodium-ion batteries using NFPP as the positive electrode still need to further solve problems such as poor rate performance and low energy density. At the same time, although the safety performance of sodium-ion batteries has been improved compared to lithium-ion batteries, there is still room for improvement.
[0004] In addition to the above-mentioned electrode material issues, the use of electrolytes and separators in sodium-ion batteries is still in its early stages. Currently, sodium-ion batteries are still using the liquid electrolyte and separator equivalent replacement model used in traditional lithium-ion batteries. However, commercial separators for lithium-ion batteries have poor thermal stability, poor wettability to sodium-ion electrolytes, and poor sodium-ion kinetics, making them unsuitable for sodium-ion battery systems. At the same time, the same requirement as for lithium-ion batteries is to increase the safety performance of the battery as much as possible.
[0005] Therefore, there is an urgent need to find and design a separator that can be compatible with the sodium-ion battery system to further improve the electrochemical performance and safety performance of sodium-ion batteries. Summary of the invention
[0006] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a modified diaphragm for a polyanion solid-state sodium battery, a preparation method thereof, and a sodium-ion battery. The present invention adopts a solid electrolyte layer and a gel electrolyte layer in coordination, and adopts an oxide solid electrolyte and a polymer solid electrolyte in coordination to modify the diaphragm, which not only enables the modified diaphragm to better adapt to the high-voltage system, improves the transmission rate and diffusion coefficient of sodium ions, thereby extending the cycle life of the polyanion solid-state sodium battery and improving the battery's rate performance and low-temperature performance, but also improves the thermal stability of the diaphragm, and eliminates the adverse effects of the positive and negative electrode contact and chemical reaction caused by thermal shrinkage of the diaphragm; in addition, while not affecting the air permeability and ensuring the dynamics, the puncture resistance of the diaphragm is also greatly improved, and the amount of liquid electrolyte added is significantly reduced, which effectively improves the safety performance of the battery and the energy density of the polyanion solid-state sodium battery.
[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0008] In a first aspect, the present invention provides a modified diaphragm for a polyanion solid-state sodium battery, the modified diaphragm comprising:
[0009] Basement membrane.
[0010] A solid electrolyte layer is provided on at least one side of the surface of the base film, and the solid electrolyte layer includes an oxide solid electrolyte and a polymer solid electrolyte.
[0011] A gel electrolyte layer is provided on an outer surface of the oxide solid electrolyte layer.
[0012] The present invention adopts oxide solid electrolyte and polymer solid electrolyte to cooperate with each other, which can further improve the liquid retention capacity of the diaphragm, and the liquid absorption rate and ionic conductivity can simultaneously improve the adhesion of the polymer solid electrolyte, and the solid electrolyte layer and the gel electrolyte layer are used to cooperate with each other, and the gel electrolyte layer can further improve the interface contact between the solid electrolyte and other materials, help it to be stably adsorbed on the diaphragm, and further improve the mechanical strength of the diaphragm, which helps the diaphragm to pass the acupuncture test. Therefore, the diaphragm is subjected to multiple modifications, which not only makes the modified diaphragm better adapted to the high-voltage system, improves the transmission rate and diffusion coefficient of sodium ions, thereby extending the cycle life of the polyanion solid-state sodium battery and improving the rate performance and low-temperature performance of the battery, but also improves the thermal stability of the diaphragm, and eliminates the adverse effects of the positive and negative electrode contact and chemical reaction caused by thermal shrinkage of the diaphragm; in addition, while not affecting the air permeability and ensuring the dynamics, the puncture resistance of the diaphragm is also greatly improved, and the amount of liquid electrolyte added is significantly reduced, which effectively improves the safety performance of the battery and the energy density of the polyanion solid-state sodium battery.
[0013] The modified diaphragm provided by the invention has strong adhesion, strong liquid absorption / retention ability and high temperature resistance.
[0014] Preferably, the base film is a polymer film, and the material of the polymer film includes polyethylene.
[0015] Preferably, the base film has a thickness of 8-10 μm, for example, 8 μm, 9 μm or 10 μm.
[0016] Preferably, the surface density of the modified membrane is 10-11 g / m 2 , for example, it can be 10g / m 2 , 10.2g / m 2 , 10.4g / m 2 10.6g / m 2 , 10.8g / m 2 or 11g / m 2 wait.
[0017] Preferably, the tensile strength of the modified diaphragm is 1800-2000 kgf / cm 2 , for example, it can be 1800kgf / cm 2 、1850kgf / cm 2 、1800kgf / cm 2 、1800kgf / cm 2 、1800kgf / cm 2 wait.
[0018] Preferably, the longitudinal shrinkage of the modified diaphragm is 0.8-1%, for example, 0.8%, 0.9% or 1%, and the transverse shrinkage is 0.2-0.25%, for example, 0.2%, 0.21%, 0.22%, 0.23%, 0.24% or 0.25%.
[0019] Preferably, the ionic conductivity of the modified membrane is 0.9-1 mS / cm, for example, 0.9 mS / cm, 0.92 mS / cm, 0.94 mS / cm, 0.96 mS / cm, 0.98 mS / cm or 1 mS / cm.
[0020] The modified membrane provided by the present invention has a surface density, tensile strength, longitudinal / transverse shrinkage rate and ionic conductivity within the above ranges, indicating that the modified membrane has sufficiently high mechanical strength and pore structure.
[0021] Preferably, the thickness of the solid electrolyte layer is 2-4 μm, for example, 2 μm, 3 μm or 4 μm.
[0022] In the present invention, a solid electrolyte layer with an appropriate thickness helps to improve the wettability of the electrolyte.
[0023] Preferably, in the solid electrolyte layer, the mass proportion of the oxide solid electrolyte is 20-30%, for example, it may be 20%, 22%, 24%, 26%, 28% or 30%.
[0024] In the present invention, an oxide solid electrolyte with a suitable mass ratio helps to increase the ion migration number in the solid electrolyte layer.
[0025] Preferably, the oxide solid electrolyte includes any one of perovskite oxide, garnet oxide or NASICON oxide, or a combination of at least two thereof. For example, the perovskite oxide may be, for example, lithium lanthanum titanium oxide (LiLaTiO4), and the garnet oxide may be, for example, Li7La3Zr2O 12 wait.
[0026] Preferably, the NASICON type oxide comprises LATP (lithium aluminum titanium phosphate).
[0027] Preferably, the ionic conductivity of the LATP is 0.4-0.8 mS / cm, for example, 0.4 mS / cm, 0.5 mS / cm, 0.6 mS / cm, 0.7 mS / cm or 0.8 mS / cm.
[0028] Preferably, the particle size D50 of the LATP is 90-130 nm, for example, 90 nm, 100 nm, 110 nm, 120 nm or 130 nm.
[0029] Preferably, the polymer solid electrolyte includes a polyvinylidene fluoride-based solid electrolyte and / or a polyacrylonitrile solid electrolyte.
[0030] Preferably, the polyvinylidene fluoride-based solid electrolyte includes polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.
[0031] Preferably, the material of the gel electrolyte layer includes any one of polyvinylidene fluoride, polyacrylonitrile or polysiloxane, or a combination of at least two thereof.
[0032] Preferably, the material of the gel electrolyte layer further includes nanofillers, and the nanofillers include any one of silicon dioxide, aluminum oxide or barium titanate, or a combination of at least two thereof.
[0033] In the present invention, the nanofiller is introduced into the gel electrolyte layer, which can increase the mechanical strength of the gel electrolyte layer and improve the ionic conductivity, and can also improve the interface compatibility between the gel electrolyte layer and the electrode and enhance the wettability of the electrolyte.
[0034] Preferably, in the gel electrolyte layer, the mass proportion of the nanofiller is 25-35%, for example, 25%, 30% or 35%.
[0035] In the present invention, nanofillers with an appropriate mass ratio in the gel electrolyte layer can maximize the mechanical strength of the gel electrolyte layer and improve its ion conductivity.
[0036] Preferably, the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:(0.5-0.7), for example, it may be 1:0.5, 1:0.6 or 1:0.7.
[0037] In the present invention, if the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is too small, that is, the thickness of the solid electrolyte layer is too small, it cannot meet the demand for improving the ion conduction rate, or the thickness of the gel electrolyte layer is too large, resulting in an increase in the thickness of the diaphragm, increasing the impedance, and reducing the lithium ion diffusion kinetics; if the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is too large, that is, the thickness of the solid electrolyte layer is too large, it will cause problems such as diaphragm pore blockage and ion diffusion obstruction. Therefore, it is necessary to adjust the thickness ratio of the solid electrolyte layer and the gel electrolyte layer to achieve a stable solid-solid interface, improve the lithium ion diffusion kinetics, and thus extend the cycle life of the battery.
[0038] In a second aspect, the present invention provides a method for preparing a modified diaphragm for a polyanion solid-state sodium battery as described in the first aspect, the preparation method comprising the following steps:
[0039] (1) An oxide solid electrolyte, a polymer solid electrolyte and a solvent are mixed to obtain a solid electrolyte material.
[0040] (2) coating a solid electrolyte material on at least one side of the base film, then coating a layer of gel electrolyte, and drying to obtain the modified diaphragm for the polyanion solid-state sodium battery.
[0041] Preferably, during the mixing process in step (1), a modifier is also added, and the modifier includes polyvinyl pyrrolidone.
[0042] Preferably, the modifier accounts for 0.2-0.7% of the total mass of the oxide solid electrolyte and the polymer solid electrolyte, for example, it may be 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or 0.7%.
[0043] In the present invention, a suitable content of the modifier helps solubilization / agglomeration and improves the dispersibility of the solid electrolyte.
[0044] Preferably, the mixing process in step (1) is accompanied by stirring, and the stirring rate is 700-900 rpm, for example, 700 rpm, 800 rpm or 900 rpm.
[0045] Preferably, the solvent in step (1) comprises N-methylpyrrolidone.
[0046] Preferably, the method for coating the solid electrolyte material in step (2) comprises any one of blade coating, spin coating or roll coating, or a combination of at least two of them.
[0047] Preferably, before coating a layer of gel electrolyte in step (2), the surface of the solid electrolyte coating is firstly soaked with an organic solvent.
[0048] In the present invention, the purpose of using an organic solvent to saturate the surface of the solid electrolyte coating is to provide an organic solvent environment, increase dispersibility, and help improve the surface adsorption when coating different materials.
[0049] Preferably, the organic solvent comprises acetone.
[0050] Preferably, the coating method of the gel electrolyte in step (2) includes a doctor blade coating method or a dipping method.
[0051] Preferably, the drying temperature in step (2) is 40-60°C, for example, 40°C, 50°C or 60°C.
[0052] Preferably, the preparation method comprises the following steps:
[0053] (1) A polymer solid electrolyte and a solvent are mixed, and the mixture is stirred in a vacuum until they are completely dissolved. Then, an oxide solid electrolyte and a modifier are added, and the mixture is stirred until the mixture is uniform, thereby obtaining a solid electrolyte material.
[0054] The modifier accounts for 0.2-0.7% of the total mass of the oxide solid electrolyte and the polymer solid electrolyte.
[0055] (2) The solid electrolyte material is coated on at least one side of the base film by a scraping method, and then the surface of the solid electrolyte material coating is fully impregnated with an organic solvent, followed by coating a layer of gel electrolyte material composed of a gel electrolyte and a nanofiller, and then vacuum drying at 40-60° C. for 4-6 hours to obtain the modified diaphragm for the polyanion solid-state sodium battery.
[0056] It should be noted that the positive electrode material of the polyanion solid-state sodium battery used in the modified diaphragm provided by the present invention is a polyanion compound. For example, it can be a phosphate (such as Na3V2(PO4)3), a fluorophosphate (such as Na2FePO4F) or a NASICON compound (such as Na3Zr2Si2PO 12 )wait.
[0057] The present invention does not specifically limit the thickness of the modified separator in the polyanion solid-state sodium battery, and illustratively it may be 12-16 μm, for example, it may be 12 μm, 13 μm, 14 μm, 15 μm or 16 μm, etc.
[0058] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] The present invention adopts a solid electrolyte layer and a gel electrolyte layer in coordination, and adopts an oxide solid electrolyte and a polymer solid electrolyte in coordination to modify the diaphragm, which not only enables the modified diaphragm to better adapt to the high-voltage system and improve the transmission rate and diffusion coefficient of sodium ions, thereby extending the cycle life of the polyanion solid-state sodium battery and improving the battery's rate performance and low-temperature performance, but also improves the thermal stability of the diaphragm, and eliminates the adverse effects of positive and negative electrode contact and chemical reactions caused by thermal shrinkage of the diaphragm; in addition, while not affecting the air permeability and ensuring the dynamics, the puncture resistance of the diaphragm is greatly improved, the amount of liquid electrolyte added is significantly reduced, and the safety performance of the battery and the energy density of the polyanion solid-state sodium battery are effectively improved. DETAILED DESCRIPTION
[0061] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0062] Example 1
[0063] This embodiment provides a modified diaphragm for a polyanion solid-state sodium battery, the modified diaphragm comprising:
[0064] The base film is a polymer film made of polyethylene and has a thickness of 9 μm.
[0065] The solid electrolyte layer is arranged on the two side surfaces of the base film, and has a thickness of 3μm; the solid electrolyte layer includes an oxide solid electrolyte and a polymer solid electrolyte, the mass proportion of the oxide solid electrolyte is 25%, the oxide solid electrolyte is LATP (ionic conductivity is 0.6mS / cm, particle size D50 is 110nm), and the polymer solid electrolyte is polyvinylidene fluoride PVDF.
[0066] The gel electrolyte layer is arranged on the outer surface of the oxide solid electrolyte layer, and the material is polyvinylidene fluoride. The thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:0.5.
[0067] This embodiment also provides a method for preparing the modified diaphragm for the above-mentioned polyanion solid-state sodium battery, and the preparation method comprises the following steps:
[0068] (1) Polyvinylidene fluoride and N-methylpyrrolidone are mixed, and vacuum stirred until they are completely dissolved, and then LATP is added, and stirred and mixed until the mixture is uniform, thereby obtaining a solid electrolyte material.
[0069] (2) coating a solid electrolyte material on one side of the polymer film by a doctor blade method, then soaking the surface of the solid electrolyte material coating with an organic solvent, acetone, and then coating a layer of a gel electrolyte material composed of polyvinylidene fluoride by a doctor blade method, and vacuum drying at 50° C. for 5 h to form a solid electrolyte layer and a gel electrolyte layer;
[0070] Repeat the above steps to sequentially coat the other side surface of the polymer film to form a solid electrolyte layer and a gel electrolyte layer to obtain the modified separator for the polyanion solid-state sodium battery.
[0071] Example 2
[0072] This embodiment provides a modified diaphragm for a polyanion solid-state sodium battery, the modified diaphragm comprising:
[0073] The base film is a polymer film made of polyethylene and has a thickness of 9 μm.
[0074] The solid electrolyte layer is arranged on one side surface of the base film and has a thickness of 3; the solid electrolyte layer includes an oxide solid electrolyte and a polymer solid electrolyte, the mass proportion of the oxide solid electrolyte is 20%, the oxide solid electrolyte is LATP (ionic conductivity is 0.6mS / cm, particle size D50 is 110nm), and the polymer solid electrolyte is polyvinylidene fluoride-hexafluoropropylene copolymer.
[0075] The gel electrolyte layer is arranged on the outer surface of the oxide solid electrolyte layer, and the material is polyvinylidene fluoride. The thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:0.67.
[0076] This embodiment also provides a method for preparing the modified diaphragm for the above-mentioned polyanion solid-state sodium battery, and the preparation method comprises the following steps:
[0077] (1) Mix polyvinylidene fluoride-hexafluoropropylene copolymer and N-methylpyrrolidone, stir them in vacuum until they are completely dissolved, then add LATP, stir and mix until the mixture is uniform, and obtain a solid electrolyte material.
[0078] (2) The solid electrolyte material is coated on one side of the polymer film by a scraping method, and then the surface of the solid electrolyte material coating is soaked with an organic solvent acetone, and then a layer of gel electrolyte material composed of polyvinylidene fluoride is coated by a scraping method, and then vacuum dried at 50° C. for 5 hours to form a solid electrolyte layer and a gel electrolyte layer, thereby obtaining the modified diaphragm for the polyanion solid-state sodium battery.
[0079] Example 3
[0080] This embodiment provides a modified diaphragm for a polyanion solid-state sodium battery, the modified diaphragm comprising:
[0081] The base film is a polymer film made of polyethylene and has a thickness of 9 μm.
[0082] The solid electrolyte layer is arranged on one side surface of the base film and has a thickness of 4 μm. The solid electrolyte layer includes an oxide solid electrolyte and a polymer solid electrolyte. The mass proportion of the oxide solid electrolyte is 30%. The oxide solid electrolyte is LATP (with an ionic conductivity of 0.6 mS / cm and a particle size D50 of 110 nm), and the polymer solid electrolyte is polyacrylonitrile.
[0083] The gel electrolyte layer is arranged on the outer surface of the oxide solid electrolyte layer, and the material is polyvinylidene fluoride. The thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:0.7.
[0084] This embodiment also provides a method for preparing the modified diaphragm for the above-mentioned polyanion solid-state sodium battery, and the preparation method comprises the following steps:
[0085] (1) Polyacrylonitrile and N-methylpyrrolidone are mixed, and vacuum stirred at 800 rpm until they are completely dissolved, and then LATP is added, and stirred and mixed at 800 rpm until the mixture is uniformly mixed to obtain a solid electrolyte material.
[0086] (2) The solid electrolyte material is coated on one side of the polymer film by a scraping method, and then the surface of the solid electrolyte material coating is soaked with an organic solvent acetone, and then a layer of gel electrolyte material composed of polyvinylidene fluoride is coated by a scraping method, and then vacuum dried at 50° C. for 5 hours to form a solid electrolyte layer and a gel electrolyte layer, thereby obtaining the modified diaphragm for the polyanion solid-state sodium battery.
[0087] Example 4
[0088] The difference between this embodiment and embodiment 2 is that a modifier is also added during the addition of LATP in step (1), wherein the modifier is polyvinyl pyrrolidone, and the modifier accounts for 0.5% of the total mass of the polyvinylidene fluoride-hexafluoropropylene copolymer and LATP.
[0089] The rest of the preparation methods and parameters were the same as those in Example 2.
[0090] Example 5
[0091] The difference between this embodiment and embodiment 2 is that the gel electrolyte material in step (2) is composed of polyvinylidene fluoride and nanofiller, the mass proportion of the nanofiller is 30%, and the nanofiller is silicon dioxide.
[0092] The rest of the preparation methods and parameters were the same as those in Example 2.
[0093] Example 6
[0094] The difference between this embodiment and embodiment 2 is that the amount of LATP added to the solid electrolyte layer is adjusted so that the mass proportion of the oxide solid electrolyte is 15%.
[0095] The rest of the preparation methods and parameters were the same as those in Example 2.
[0096] Example 7
[0097] The difference between this embodiment and embodiment 2 is that the amount of LATP added to the solid electrolyte layer is adjusted so that the mass proportion of the oxide solid electrolyte is 35%.
[0098] The rest of the preparation methods and parameters were the same as those in Example 2.
[0099] Example 8
[0100] The difference between this embodiment and embodiment 2 is that the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:4.
[0101] The rest of the preparation methods and parameters were the same as those in Example 2.
[0102] Example 9
[0103] The difference between this embodiment and embodiment 2 is that the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:0.25.
[0104] The rest of the preparation methods and parameters were the same as those in Example 2.
[0105] Example 10
[0106] The difference between this embodiment and embodiment 4 is that the modifier in step (1) accounts for 0.1% of the total mass of the polyvinylidene fluoride-hexafluoropropylene copolymer and LATP.
[0107] The rest of the preparation methods and parameters were the same as those in Example 4.
[0108] Embodiment 11
[0109] The difference between this embodiment and embodiment 4 is that the modifier in step (1) accounts for 0.8% of the total mass of the polyvinylidene fluoride-hexafluoropropylene copolymer and LATP.
[0110] The rest of the preparation methods and parameters were the same as those in Example 4.
[0111] Example 12
[0112] The difference between this embodiment and embodiment 5 is that the mass proportion of the nanofiller is 20%.
[0113] The rest of the preparation methods and parameters were the same as those in Example 5.
[0114] Embodiment 13
[0115] The difference between this embodiment and embodiment 5 is that the mass proportion of the nanofiller is 40%.
[0116] The rest of the preparation methods and parameters were the same as those in Example 5.
[0117] Comparative Example 1
[0118] The difference between this comparative example and Example 2 is that the solid electrolyte layer is composed of only oxide solid electrolyte, that is, polyvinylidene fluoride-hexafluoropropylene copolymer is not added in step (1).
[0119] The rest of the preparation methods and parameters were the same as those in Example 2.
[0120] Comparative Example 2
[0121] The difference between this comparative example and Example 2 is that no gel electrolyte layer is provided, that is, no gel electrolyte material is coated in step (2).
[0122] The rest of the preparation methods and parameters were the same as those in Example 2.
[0123] Comparative Example 3
[0124] This comparative example provides a polyethylene film as described in Example 2 as a separator.
[0125] Performance Testing
[0126] The modified diaphragm provided in the above embodiments and comparative examples is assembled with the positive electrode plate, the negative electrode plate and the electrolyte to obtain a polyanion solid-state sodium battery; wherein the positive electrode material in the positive electrode plate is sodium iron pyrophosphate, the negative electrode material in the negative electrode plate is a hard carbon material, and the electrolyte is a commercial NaPF6-based electrolyte.
[0127] The above sodium ion batteries were tested for cycle performance, rate performance and safety performance.
[0128] The test conditions for the cycle performance include: current 0.1C, voltage 2.5-4.2V.
[0129] The test conditions for rate performance include: 0.1 / 0.2 / 0.5 / 1 / 3 / 5C.
[0130] The safety performance is tested by needle puncture test.
[0131] The above test results are shown in Table 1.
[0132] Table 1
[0133]
[0134]
[0135] analyze:
[0136] As can be seen from the above table, the present invention adopts a solid electrolyte layer and a gel electrolyte layer in coordination, and an oxide solid electrolyte and a polymer solid electrolyte in coordination to modify the diaphragm, which not only enables the modified diaphragm to better adapt to the high-voltage system and improve the transmission rate and diffusion coefficient of sodium ions, thereby extending the cycle life of the battery and improving the battery's rate performance and low-temperature performance, but also improves the thermal stability of the diaphragm, and eliminates the adverse effects of positive and negative electrode contact and chemical reactions caused by thermal shrinkage of the diaphragm; in addition, while not affecting the air permeability and ensuring the dynamics, the puncture resistance of the diaphragm is greatly improved, and the amount of liquid electrolyte added is significantly reduced, which effectively improves the safety performance of the battery.
[0137] It can be seen from Example 2 and Examples 4-5 that if a modifier is added during the addition of LATP, it helps dispersion and improves adhesion; if the gel electrolyte material is composed of polyvinylidene fluoride and nanofillers, the introduction of nanofillers helps prevent thermal shrinkage, improves interface stability, and thus improves ion conduction.
[0138] It can be seen from Example 2 and Examples 6-7 that if the mass proportion of the oxide solid electrolyte is too small, it is not conducive to improving battery performance; if the mass proportion of the oxide solid electrolyte is too large, it is not conducive to improving heat resistance and mechanical strength.
[0139] It can be seen from Example 2 and Examples 8-9 that if the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is too small, it is not conducive to improving battery performance; if the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is too large, it is not conducive to improving safety performance.
[0140] It can be seen from Examples 4 and 10-11 that if the proportion of the modifier to the total mass of polyacrylonitrile and LATP is too small, it is not conducive to improving the dispersion effect; if the proportion of the modifier to the total mass of polyacrylonitrile and LATP is too large, it is not conducive to preparing the slurry and improving the compaction density of the electrode.
[0141] It can be seen from Example 5 and Examples 12-13 that if the mass proportion of the nanofiller is too small, it will not be conducive to effectively improving the heat resistance of the diaphragm and the wettability of the electrolyte; if the mass proportion of the nanofiller is too large, it will be detrimental to ion diffusion.
[0142] It can be seen from Example 2 and Comparative Examples 1-2 that if the solid electrolyte layer is composed only of an oxide solid electrolyte, the adhesion is poor; if the gel electrolyte layer is not provided, the adhesion is poor and the safety performance is poor.
[0143] It can be seen from Example 2 and Comparative Example 3 that if only a polyethylene film is used as a separator, the cycle performance and safety performance are poor.
[0144] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A modified diaphragm for a polyanion solid-state sodium battery, characterized in that: The modified diaphragm comprises: Basement membrane; A solid electrolyte layer, the solid electrolyte layer is arranged on at least one side surface of the base film, and the solid electrolyte layer includes an oxide solid electrolyte and a polymer solid electrolyte; A gel electrolyte layer is provided on an outer surface of the oxide solid electrolyte layer.
2. The modified diaphragm according to claim 1, characterized in that: The base film is a polymer film, and the material of the polymer film includes polyethylene; Preferably, the base film has a thickness of 8-10 μm.
3. The modified diaphragm according to claim 1 or 2, characterized in that: The surface density of the modified diaphragm is 10-11 g / m 2 ; Preferably, the tensile strength of the modified diaphragm is 1800-2000 kgf / cm 2 ; Preferably, the longitudinal shrinkage of the modified diaphragm is 0.8-1%, and the transverse shrinkage is 0.2-0.25%; Preferably, the ionic conductivity of the modified membrane is 0.9-1 mS / cm.
4. The modified diaphragm according to any one of claims 1 to 3, characterized in that: The thickness of the solid electrolyte layer is 2-4 μm; Preferably, in the solid electrolyte layer, the mass proportion of the oxide solid electrolyte is 20-30%; Preferably, the oxide solid electrolyte comprises any one or a combination of at least two of perovskite-type oxide, garnet-type oxide or NASICON-type oxide; Preferably, the NASICON-type oxide comprises LATP; Preferably, the polymer solid electrolyte includes a polyvinylidene fluoride-based solid electrolyte and / or a polyacrylonitrile-based solid electrolyte; Preferably, the polyvinylidene fluoride-based solid electrolyte includes polyvinylidene fluoride and / or polyvinylidene fluoride-hexafluoropropylene copolymer.
5. The modified diaphragm according to any one of claims 1 to 4, characterized in that: The material of the gel electrolyte layer includes any one of polyvinylidene fluoride, polyacrylonitrile or polysiloxane or a combination of at least two thereof; Preferably, the material of the gel electrolyte layer further comprises a nanofiller, and the nanofiller comprises any one or a combination of at least two of silicon dioxide, aluminum oxide or barium titanate; Preferably, in the gel electrolyte layer, the mass percentage of the nanofiller is 25-35%; Preferably, the thickness ratio of the solid electrolyte layer to the gel electrolyte layer is 1:(0.5-0.7).
6. A method for preparing a modified diaphragm for a polyanion solid-state sodium battery according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: (1) mixing an oxide solid electrolyte, a polymer solid electrolyte and a solvent to obtain a solid electrolyte material; (2) coating a solid electrolyte material on at least one side of the base film, then coating a layer of gel electrolyte, and drying to obtain the modified diaphragm for the polyanion solid-state sodium battery.
7. The preparation method according to claim 6, characterized in that: During the mixing process of step (1), a modifier is also added, wherein the modifier comprises polyvinyl pyrrolidone; Preferably, the modifier accounts for 0.2-0.7% of the total mass of the oxide solid electrolyte and the polymer solid electrolyte.
8. The preparation method according to claim 6 or 7, characterized in that: The mixing process in step (1) is accompanied by stirring, and the stirring rate is 700-900 rpm.
9. The preparation method according to any one of claims 6 to 8, characterized in that: The method of coating the solid electrolyte material in step (2) comprises any one of scraping, spin coating or roll coating, or a combination of at least two thereof; Preferably, before applying a layer of gel electrolyte in step (2), the surface of the solid electrolyte coating is firstly soaked with an organic solvent; Preferably, the organic solvent comprises acetone; Preferably, the coating method of the gel electrolyte in step (2) includes a scraping method or a dipping method; Preferably, the drying temperature in step (2) is 40-60°C.
10. The preparation method according to any one of claims 6 to 9, characterized in that: The preparation method comprises the following steps: (1) mixing a polymer solid electrolyte and a solvent, stirring them in a vacuum until they are completely dissolved, then adding an oxide solid electrolyte and a modifier, stirring and mixing until the mixture is uniform, to obtain a solid electrolyte material; Wherein, the modifier accounts for 0.2-0.7% of the total mass of the oxide solid electrolyte and the polymer solid electrolyte; (2) The solid electrolyte material is coated on at least one side of the base film by a scraping method, and then the surface of the solid electrolyte material coating is fully impregnated with an organic solvent, followed by coating a layer of gel electrolyte material composed of a gel electrolyte and a nanofiller, and then vacuum drying at 40-60° C. for 4-6 hours to obtain the modified diaphragm for the polyanion solid-state sodium battery.
Citation Information
Cited By
Lithium-manganese battery
CN121507318A